Toward standardization of the cut‐off value for the direct immunobead test using the postcoital test in immunologically infertile males. (9th August 2012) - Koriyama, Junko; Shibahara, Hiroaki; Ikeda, Tomoe; Hirano, Yuki; Suzuki, Tatsuya; Suzuki, Mitsuaki
Abstract: Purpose: There is a need to improve our understanding of the cut‐off value of the direct immunobead test (D‐IBT). Methods: The subjects were 26 D‐IBT‐positive and 140 D‐IBT‐negative males. The results of post coital tests (PCTs) for each subject were examined. Results: A significant difference was observed in abnormal PCTs between values <20 % and those ≥20 % ( P = 0.02). However, there was no significant difference in abnormal PCTs between values <50 % and those ≥50 % ( P = 0.084). Conclusions: A cut‐off value of 20 % was correlated with the possibility of conception on treatment with IUI. The D‐IBT is a screening test, and the value of 20 % initially suggested by Bronson et al. seems to be more appropriate than that of 50 % in the criteria defined by the World Health Organization.